Essential factors for the changes in concrete during electrochemical extraction - Alsabry, Abdrahman (Zielona Góra: Uniwersytet Zielonogórski)
The objective of the article is to present one of the most significant factors affecting electrochemical removal of chloride ions from concrete. Based on the literature findings, tests were carried out on specimens containing chloride admixtures introduced to the cement grout, on elements subjected to chloride penetration from the solution in laboratory conditions and on fragments of constructions penetrated by chlorides as a result of a long-term exposure to seawater.
Keywords: chloride ion penetration; electrochemical extraction; conrete; seawater